PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MODEL DISCOVERY LEARNING MELALUI MEDIA KUBUS SATUAN PADA SISWA KELAS V SDN KAUMAN 1 MALANG - Pujo Setyo Aji; Erna Yayuk; Novi Qurrata A'yunin (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This study aimed to improve students’ learning outcomes of mathematics by using learning discovery models through the media of the cube unit in class V students of SDN Kauman 1 Malang City. Students still faced difficulty in developing the concept of building volume (cubes and cuboid). The form of research conducted in this study used Classroom Action Research (CAR) design developed by Kemmis and Mc. Taggart. The subjects in this study were 32 students of fifth-grade students of SDN Kauman 1 Malang in 2018/2019. This research was conducted in two cycles, namely, cycle I and cycle II. Data collection techniques employed interviews, tests, and observations. The data from the research results obtained through the process of interviews, tests, and observations. In the first cycle the students’ mathematics learning outcomes increased that was based on the results of the cycle, with the average value of students at 66.72 increased to be 78.28 in the first cycle, and 92.28 in the second cycle with the percentage of completeness of 40.62% in the cycle, it changed 62.50% in the first cycle and 87.50% in the second cycle. Thus, the study yielded the result showing that the model of learning discovery through media cube unit can improve students' mathematics learning outcomes.